The role of epiphytes in seagrass productivity under ocean acidification - Johanna Berlinghof; Friederike Peiffer; Ugo Marzocchi; Marco Munari; Grazia M. Quero; Laura Dennis; Christian Wild; Ulisse Cardini (Scientific Reports, 2022)
Abstract Ocean Acidification (OA), due to rising atmospheric CO2, can affect the seagrass holobiont by changing the plant's ecophysiology and the composition and functioning of its epiphytic community. However, our knowledge of the role of epiphytes in the productivity of the seagrass holobiont in response to environmental changes is still very limited. CO2 vents off Ischia Island (Italy) naturally reduce seawater pH, allowing to investigate the adaptation of the seagrass Posidonia oceanica L. (Delile) to OA. Here, we analyzed the percent cover of different epiphytic groups and the epiphytic biomass of P. oceanica leaves, collected inside (pH 6.9–7.9) and outside (pH 8.1–8.2) the CO2 vents. We estimated the contribution of epiphytes to net primary production (NPP) and respiration (R) of leaf sections collected from the vent and ambient pH sites in laboratory incubations. Additionally, we quantified net community production (NCP) and community respiration (CR) of seagrass communities in situ at vent and ambient pH sites using benthic chambers. Leaves at ambient pH sites had a 25% higher total epiphytic cover with encrusting red algae (32%) dominating the community, while leaves at vent pH sites were dominated by hydrozoans (21%). Leaf sections with and without epiphytes from the vent pH site produced and respired significantly more oxygen than leaf sections from the ambient pH site, showing an average increase of 47 ± 21% (mean ± SE) in NPP and 50 ± 4% in R, respectively. Epiphytes contributed little to the increase in R; however, their contribution to NPP was important (56 ± 6% of the total flux). The increase in productivity of seagrass leaves adapted to OA was only marginally reflected by the results from the in situ benthic chambers, underlining the complexity of the seagrass community response to naturally occurring OA conditions.